Immunological effects of autohemo vaccination and autogenous vaccination in bovine with cutaneous papillomatosis virus - Suárez-Usbeck, Andrés; Vinueza, Pamela; Mora, Marilyn; Carrasco, Anahí; Echeverria, Tirsa; Vela, Andrea (Revista Colombiana de Ciencias Pecuarias, 2025)
Papillomavirus is a viral pathogen known to instigate the development of benign tumors in mammalian hosts. Various therapeutic approaches exist for managing cutaneous papilloma resulting from bovine papillomavirus (BPV) Autohemovaccine (AHV), and autogenous vaccine (ATV) stands as one such method. The aim of research was to scrutinize the immunological effects of AHV and ATV in cattle in Ecuador. 150 cattle with symptoms of cutaneous were diagnosed using PCR and distributed among different groups. To create the vaccines, n= 25 were used in AHV protocol with 20 mL and n=25 with 10 mL blood doses administered to them, n= 25 were used in 10 mL and 20 mL in ATV protocol. ATV vaccines were prepared by adding 0.5% formalin to the suspension, which was topped up by crystal penicillin. The vaccines were stored at 4°C until used. Vaccines (AHV & ATV) were administered 4 times subcutaneous at 1-week intervals in 20 and 10 mL dosages, respectively. Hematological and immunological analyses were performed by collecting the blood samples before and after each vaccination. while the remaining subjects (n=50) will serve as positive control group (C+). The findings demonstrated in ATV (10 and 20 mL) and AHV (10 and 20 mL) a notable surge in leukocyte (14.5; 14; 15.4; 16 103/mm3), lymphocyte (55; 52; 58; 62 %), and interleukin-6 (0.85; 0.80; 0.95; 0.97 ng/L), Neutrophil (33; 35; 44; 40%) and Monocyte (5; 8; 12; 13 %) compared with C+ (Leu: 13 103/mm3; Lym: 50 %; IL-6: 0.54 ng/L; Neu: 34%; Mon: 6.5%) . In AHV and ATV, encouragingly, within the first month post-vaccination, signs of regression in cutaneous papilloma became evident. As a conclusion, bovine papillomatosis represents a condition of considerable economic significance within the domain of dairy farming. The study underscores autogenous vaccination as a pragmatic therapeutic intervention, effectively prompting lesion regression, particularly through the stimulation of IL-6 and lymphocyte production in cattle infected with papillomavirus.